Control of chlorophyll synthesis - Tewiah, T (1969)

(untitled)
1. Peperomia magnolaefolia, the main plant material used in the work reported in this thesis, possesses succulent leaves which show a periclinal chimera. The anatomy of the leaves, and the occurrence of 'bud-variations' which were found in the course of the work is to indicate that their periclinal struetare is a mesochimera